Analisis Kelayakan Usaha Tape Singkong Sumber Madu sebagai Oleh-Oleh Khas Kabupaten Jember - Dwi Wahid Fitrianto; Afrijal Ramadani; Revanda Marissa; Eki Dwi Eksanti; Anggi Kharisma Putri; Septia Ningsih; Rafa Aditya Nur R; Ainnur Iqtaara Meilani; Saidatus Sholeha; Oryza Ardhiarisca (AKUNTANSI 45, 2026)
The cassava tape business is one of the food MSME sectors with potential as a distinctive local souvenir product in Jember Regency, featuring relatively stable market demand that increases at certain times. The Tape Sumber Madu business demonstrates rapid product turnover and is supported by a distribution system involving product consignment, direct sales, and online marketing. From a technical perspective, the production process is still carried out traditionally with limited capacity and a reliance on labor, while from a management and legal perspective, the business has legal standing but financial management remains rudimentary. From a social and environmental perspective, this business has a positive impact through job creation and the utilization of production waste as livestock feed. The analysis was conducted descriptively using both qualitative and quantitative approaches through interviews and business feasibility calculations. The financial analysis shows a Cost of Goods Sold (COGS) of Rp11,000 per box with a selling price of Rp17,000, a profit of Rp480,000 per production run, and a B/C Ratio of 1.54, indicating that the business is profitable. Overall, the Tape Sumber Madu business is deemed viable and has good development prospects, with a need to improve production efficiency, management practices, and marketing strategies to support the sustainability of the business.